Peace-Oriented Electoral Campaigns and Political Victory: Evidence from Three Local Elections in Post-Conflict Mamasa - Mahyuddin, Mahyuddin; Nizah, Mohd Azmir Mohd; Mohad, Abdul Hakim; Rasyid, Abd (JPP (Jurnal Politik Profetik), 2026)
This article explores the impact of peace-oriented electoral campaigns on the attainment of political victories in post-conflict regions, drawing upon empirical evidence from three local elections in Mamasa, Eastern Indonesia. In the early 2000s, Mamasa experienced a period of significant communal and religious tensions, which led to the emergence of a contested arena where reconciliation narratives, tolerance politics, and cultural traditions intersected with electoral competition. Prior studies on post-conflict elections in Indonesia have predominantly focused on institutional reforms or power-sharing mechanisms. Conversely, there has been limited attention paid to campaign discourses as instruments of peacebuilding and political legitimacy. The present study employs a qualitative case study design, conducting in-depth interviews with political elites, religious leaders, and community representatives. This approach is complemented by a thorough document analysis of campaign materials and electoral data. The findings indicate that candidates who consistently framed their campaigns around reconciliation, interfaith solidarity, and inclusive development were more likely to secure broad-based support across religious and ethnic lines. The analysis demonstrates that peace-oriented narratives functioned as symbolic capital, reducing residual distrust and legitimizing leadership in a fragile political landscape. Furthermore, the study emphasizes the dynamic interaction between local cultural institutions, religious authorities, and electoral strategies in sustaining post-conflict stability. This research contributes to broader debates on the nexus between peacebuilding and democratization, offering insights into how political campaigns can move beyond identity-based competition toward inclusive governance.